Physiological and Psychological Profiles of Elite Iranian Badminton Players - Zohreh Kamyab; Mehrali Hemati; Farhad Rahmani; Bahador Zakizadeh (University of Tehran, 2010)
The aim of this research was to provide physiological and psychological profiles of elite Iranian badminton players. 18 elite badminton players (8 females aged 19.12±3.09 years, and 10 males aged 19.8±2.93 years) took part in this research. The physiological features measured included aerobic power (gas analyzer), anaerobic alactacid power (Wingate), leg muscle power (Sargent vertical jump), leg muscle endurance (bilateral couple jump), abdomen endurance (sit-ups), speed (40 yd running), agility (4×9 m and Illinois running), reaction time and flexibility (sit and reach). Also, the mental preparation of the subjects were measured by the psychological questionnaire "SASI Psych". For statistical analysis of the data, independent t test and single group student test was used. According to the results, the females were significantly weaker than males in physical fitness and mental preparation (P